The Effect of Family Functioning on Aggressive Behavior in Adolescents in Medan City - fatma indriani; Raras Sutatminingsih; Eka Ervika (Universitas Islam Negeri Sumatera Utara, Medan, 2021)
Aggressive behavior in adolescents is an issue that is of concern to mental health practitioners and educators. Aggressive behavior is often found in big cities. Aggressive behavior in adolescents also occurs in the city of Medan. Several previous studies have shown that there is a relationship between family factors and aggressive behavior. The purpose of the study was to determine the effect of family functioning on aggressive behavior in adolescents in the city of Medan. Data were obtained from 263 middle-aged adolescents who lived in the city of Medan with an age range of 15-18 years. Sampling was done by using a non-random sampling technique, namely the incidental sampling technique. In this study, data collection was carried out using a scale as a measuring tool, namely the aggressive behavior scale and the family functioning scale. Data were analyzed using simple regression method. The results showed that there was a negative influence of family functioning on aggressive behavior. From the results of this study, it can be concluded that the healthier the functioning of the family owned by adolescents, the lower the tendency to display aggressive behavior and vice versa, the more unhealthy the functioning of the family, the higher the tendency to engage in aggressive behavior. in adolescents. The suggestion from this research is that parents and adolescents can build and establish a harmonious relationship and play a good role according to their respective roles in order to create a family that can function healthily which will have an impact on decreasing aggressive behavior